Variation in grain yield, protein content and other agronomic characters in mungbean (Vigna radiata (L) wilczek) - Quah, S. C.; Sidek, M. S. M; Mat, C. H. C. (SABRAO (Society for the Advancement of Breeding Researches in Asia and Oceania), 1983)
A breeding program was initiated in Universiti Pertanian in 1979 with the main objectives of evaluating existing varieties and to develop new varieties through breeding and selection. Several varieties were tested for their response to nitrogen fertilization, and seven varieties were chosen for hybridization to generate all possible combinations. It was found that nitrogen fertilization up to 60 kg/ha failed to increase either the grain yield or the protein content of mungbean varieties. Heterosis was however observed for grain yield, protein content, number of pods per plant, length of pods, number of seeds per plant and days to flowering in the F1 hybrids. Segregation for some of these characters was also observed in F2 and F 3 crosses grown in 1980. The results of the above experiments are discussed in relation 10 existing varieties.